A method for preparing a metal mesh enclosure loaded PDMS membrane anti-moisture poisoning prevention sensor device

By combining screen printing and ethanol-assisted film peeling technology with gas pressure regulation, a moisture-resistant and poison-resistant PDMS film sensor was prepared, which solved the stability and selectivity problems of semiconductor gas sensors in high humidity environments and realized efficient and reliable gas detection of the sensor.

CN123029083APending Publication Date: 2026-11-03DALIAN NATIONALITIES UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611239715.1
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-11-03

AI Technical Summary

Technical Problem

Existing semiconductor gas sensors are susceptible to interference in high humidity environments, and the sensitive materials are easily poisoned. Furthermore, the thin film preparation process is difficult to achieve uniformity and reliability, which affects the long-term stability and detection accuracy of the sensors.

Method used

PDMS films are prepared using screen printing technology. Combined with ethanol-assisted non-destructive film peeling and gas pressure regulation, precise control and non-destructive transfer of PDMS film thickness are achieved. By integrating a stainless steel mesh cap and a housing, a moisture-resistant and poison-proof sensor device is formed.

Benefits of technology

The PDMS film achieves uniform density and easy transfer, improves the sensor's resistance to moisture and silicon poisoning, enhances the permeation selectivity and response stability of ethanol gas, and improves the long-term reliability and detection accuracy of the sensor.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN123029083A_ABST
    Figure CN123029083A_ABST
Patent Text Reader

Abstract

The present application belongs to the technical field of gas sensor, and relates to a preparation method of a humidity-resistant and poisoning-resistant sensor device with a metal mesh shell loaded with a PDMS film. The preparation method can accurately control the film thickness, realize non-destructive transfer and reliable packaging of the film, improve the permeation selectivity of the sensor to ethanol gas through film thickness optimization and secondary regulation, and endow the sensor with excellent humidity interference resistance, static electricity accumulation inhibition, silicon poisoning resistance and dustproof performance. The sensor device loaded with the film with an optimized thickness has excellent response stability to the target gas in a wide humidity range, is much better than the bare sensor, has excellent sensitivity retention rate in a silicon compound-containing environment, and has a response value to the target gas significantly better than that to the interference gas, thus exhibiting excellent high gas selectivity. Compared with the electroblotting and electrospinning processes, the screen printing technology adopted in the present application can form a uniform and dense film, has a wide process window, and is easy to transfer the film, thus having excellent preparation efficiency and yield.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of gas sensor technology, and more specifically relates to a method for preparing a moisture-resistant and poison-resistant sensor device with a metal mesh shell loaded with a PDMS film. Background Technology

[0002] Semiconductor gas sensors, with their advantages of high sensitivity, low power consumption, and fast response speed, are widely used for the detection of volatile organic gases such as ethanol and acetone. However, the sensitive materials of these sensors are susceptible to interference from the external environment in practical use. For example, high humidity environments can cause baseline drift and sensitivity decay; silicon-containing compounds (such as hexamethyldisiloxane) can cause irreversible poisoning of the sensitive layer; and large molecular interference gases can occupy reactive sites, causing sensor failure. These interferences severely affect the long-term stability and detection accuracy of the sensors.

[0003] To address the aforementioned issues, some existing technologies typically employ a selectively permeable membrane placed outside the sensor. This membrane utilizes physical sieving or dissolution-diffusion mechanisms to block interfering substances while allowing the target gas to pass through. Polydimethylsiloxane (PDMS) has become a commonly used membrane material due to its excellent gas permeability and hydrophobicity.

[0004] Currently, common methods for preparing PDMS thin films include spin coating, casting, electro-spraying, and electrospinning. While spin coating and casting are simple processes, the film thickness is difficult to control flexibly over a wide range, and the film is easily damaged when peeled from the substrate. Electro-spraying uses a high-voltage electric field to spray a polymer solution, but its film uniformity is affected by many factors such as solution properties, voltage, and ambient temperature and humidity. It has a narrow process window and poor thickness consistency over large areas. Furthermore, electro-sprayed films adhere tightly to the substrate, requiring special handling during peeling, often resulting in film tearing and low yield. Electrospinning stretches a polymer solution under high pressure to form a fibrous film, but the resulting fibrous film lacks density, contains microporous defects, has poor selectivity for gas molecule sieving, and has low mechanical strength, making it easily damaged during transfer and assembly. These drawbacks severely restrict the reliable application of PDMS thin films in gas sensor packaging.

[0005] There is an urgent need to develop a method for preparing PDMS films that are uniform in film formation, controllable in film thickness, easy to peel and transfer, and highly integrated with the sensor housing, in order to meet the sensor's requirements for selective ethanol permeation, moisture resistance, and silicon poisoning resistance. Summary of the Invention

[0006] The purpose of this invention is to provide a method for preparing a moisture-resistant and poison-resistant sensor device with a metal mesh shell loaded with a PDMS film. Specifically, it relates to a method for preparing a sensor device with a metal mesh shell loaded with a polydimethylsiloxane (PDMS) film for semiconductor gas sensors. This preparation method can precisely control the thickness of the PDMS film, achieve non-destructive transfer and reliable encapsulation of the film, and significantly improve the sensor's permeation selectivity for ethanol gas through film thickness optimization and secondary control. At the same time, it endows the sensor with excellent resistance to moisture interference, silicon poisoning resistance and high gas selectivity, and fundamentally solves the problem of anti-interference and long-term stability of semiconductor gas sensors in complex environments.

[0007] To achieve the above objectives, the present invention provides the following solution: One of the technical solutions of this invention is: a method for preparing a moisture-resistant and poison-resistant sensor device with a metal mesh shell loaded with a PDMS film, the steps of which include: The PDMS prepolymer and crosslinking agent are mixed evenly to obtain the PDMS prepolymer solution; The PDMS prepolymer solution was printed onto a PET release film substrate using screen printing, cured, and then peeled off non-destructively with ethanol to obtain a PDMS film. The PDMS film is covered on a stainless steel mesh cap, and after venting and bonding, it is inserted into a stainless steel shell to obtain the moisture-resistant and poison-resistant sensor device.

[0008] Furthermore, the volume ratio of the PDMS prepolymer to the crosslinking agent is 10:1.

[0009] Furthermore, the PDMS prepolymer and crosslinking agent are Dow Corning DC184, wherein the PDMS prepolymer is the main agent A in Dow Corning DC184, and the crosslinking agent is the curing agent B in Dow Corning DC184.

[0010] Furthermore, the mesh count of the screen printing stencil used for screen printing film formation is 60-150 mesh.

[0011] Furthermore, the curing temperature is 75-85℃ and the time is 30-50 min, with the preferred curing temperature being 80℃ and the time being 40 min.

[0012] Furthermore, the ethanol-assisted non-destructive film removal step includes: spraying ethanol at the opening (to eliminate van der Waals forces between the film and the substrate), waiting 3-5 seconds, and then completely removing the PDMS film.

[0013] Furthermore, the thickness of the PDMS film is 0.4-2.8 μm, preferably 0.42 μm, 1.55 μm or 2.79 μm.

[0014] The PDMS film in this invention serves as a protective film and possesses multiple functions, including hydrophobicity and breathability, protection against silicon poisoning, anti-interference (isolation of molecules with larger diameters), high selectivity, antistatic properties, and dust prevention.

[0015] Furthermore, after the stainless steel shell is inserted, a secondary film thickness adjustment process is also included.

[0016] Optionally, the secondary film thickness control process includes: applying a gas pressure of hectopascal level (400-700 Pa) to the PDMS film from the stainless steel mesh cap side, so that the film undergoes controllable stretching and thinning within the elastic range.

[0017] The second technical solution of the present invention provides a moisture-resistant and anti-poisoning sensor device with a metal mesh shell loaded with a PDMS film, wherein the moisture-resistant and anti-poisoning sensor device with a metal mesh shell loaded with a PDMS film is prepared by the above-mentioned preparation method.

[0018] The third technical solution of the present invention provides an application of the above-mentioned metal mesh shell loaded with PDMS film as a moisture-resistant and poison-resistant sensor in gas detection.

[0019] Furthermore, the gas detection includes ethanol gas detection.

[0020] The present invention discloses the following technical effects: The present invention provides a moisture-resistant and anti-poisoning sensor device and preparation method for a PDMS film loaded with a metal mesh shell. By utilizing screen printing combined with SEM cross-sectional characterization, a quantitative correspondence between screen mesh count and PDMS film thickness is established, enabling precise preparation of PDMS films of target thickness with excellent process repeatability and ease of operation. An ethanol-assisted peeling method is employed to eliminate van der Waals forces between the film and substrate, achieving complete and non-destructive peeling of the micron-sized PDMS film from the substrate. This method boasts an excellent film transfer success rate and effectively solves the problem of easy breakage during film handling. The stainless steel mesh cap provides stable mechanical support for the PDMS film while allowing free gas passage. The stainless steel shell provides excellent protection, and the overall structure is compact and easily integrated with semiconductor sensor chips. Based on simulation and experiments… Verification showed that reducing the thickness of the PDMS film can selectively and significantly enhance the permeation flux of the target gas (such as ethanol), while the effect on enhancing the permeation of small molecule interfering substances such as water vapor is very limited. The sensor with the optimized thickness of the PDMS film has excellent response stability to the target gas (such as ethanol) over a wide humidity range, which is far superior to the bare sensor. It has excellent sensitivity retention in silicon compound environments, and the response value to the target gas (such as ethanol) is significantly better than that to interfering gases (such as methanol, acetone, benzene, etc.), showing excellent resistance to moisture, silicon poisoning, and high selectivity to the target gas (such as ethanol). Compared with electro-inking and electrospinning, screen printing produces uniform and dense films with a wide process window and easy film peeling and transfer. It not only has excellent preparation efficiency and yield, but also excellent dustproof and antistatic properties. Attached Figure Description

[0021] The accompanying drawings, which form part of this invention, are used to provide a further understanding of the invention. The illustrative embodiments of the invention and their descriptions are used to explain the invention and do not constitute an undue limitation of the invention. In the drawings: Figure 1 This is a schematic diagram of the manufacturing process of the sensor device of the present invention.

[0022] Figure 2 The thickness of the cured film prepared in Examples 1-3 is given, where a represents Example 3, b represents Example 2, and c represents Example 1.

[0023] Figure 3 This is a COMSOL simulation model diagram of PDMS film thickness controlled by air pressure.

[0024] Figure 4 This is a simulated distribution diagram of ethanol osmotic concentration.

[0025] Figure 5 The response curves of the bare mesh sensor to 50 ppm ethanol under different humidity conditions are shown.

[0026] Figure 6The figures show the response curves of the sensor devices and the bare mesh sensor in Examples 1-3 to ethanol gas under different humidity levels, where a represents 20% humidity, b represents 40% humidity, c represents 60% humidity, and d represents 80% humidity.

[0027] Figure 7 The graphs show the response changes of the sensor device and the bare mesh sensor in Example 2 to 50 ppm ethanol before and after silicon vapor poisoning.

[0028] Figure 8 The graphs show the response curves for different gases.

[0029] Figure 9 Comparison of response curves for Example 2 and Example 4.

[0030] Figure 10 Let be the resistance of the stainless steel mesh and the stainless steel mesh / PDMS film, where a is the stainless steel mesh and b is the stainless steel mesh / PDMS film. Detailed Implementation

[0031] Various exemplary embodiments of the present invention will now be described in detail. This detailed description should not be considered as a limitation of the present invention, but rather as a more detailed description of certain aspects, features, and embodiments of the present invention.

[0032] It should be understood that the terminology used in this invention is merely for describing particular embodiments and is not intended to limit the invention. Furthermore, with respect to numerical ranges in this invention, it should be understood that each intermediate value between the upper and lower limits of the range is also specifically disclosed. Any stated value or intermediate value within a stated range, as well as each smaller range between any other stated value or intermediate value within said range, is also included in this invention. The upper and lower limits of these smaller ranges may be independently included or excluded from the range.

[0033] Unless otherwise stated, all technical and scientific terms used herein have the same meaning as commonly understood by one of ordinary skill in the art. While only preferred methods and materials have been described herein, any methods and materials similar or equivalent to those described herein may be used in the implementation or testing of this invention. All references to this specification are incorporated by way of citation to disclose and describe methods and / or materials associated with those references. In the event of any conflict with any incorporated reference, the content of this specification shall prevail.

[0034] Various modifications and variations can be made to the specific embodiments described in this specification without departing from the scope or spirit of the invention, as will be apparent to those skilled in the art. Other embodiments derived from this specification will also be apparent to those skilled in the art. This specification and embodiments are merely exemplary.

[0035] The terms “include,” “including,” “have,” “contain,” etc., used in this article are all open-ended terms, meaning that they include but are not limited to.

[0036] Unless otherwise specified, all raw materials and reagents involved in the specific embodiments of this invention are commercially available products.

[0037] In this invention, the PDMS prepolymer and crosslinking agent are Dow Corning DC184, wherein the PDMS prepolymer is the main agent A in Dow Corning DC184, and the crosslinking agent is the curing agent B in Dow Corning DC184.

[0038] Unless otherwise specified, room temperature and ambient temperature in the specific embodiments of this invention refer to 20-30℃.

[0039] It should be noted that any aspects not described in detail in this invention are conventional practices in the field and are not the focus of this invention.

[0040] In some specific embodiments, the present invention provides a method for preparing a moisture-resistant and poison-resistant sensor device with a metal mesh shell loaded with a PDMS film, the steps of which include: Preparation of S1 and PDMS prepolymer solution: The PDMS prepolymer and crosslinking agent were mixed evenly at a volume ratio of 10:1, and then ultrasonically degassed to obtain the PDMS prepolymer solution. S2, Screen Printing for Film Formation: Using screen printing stencils with different mesh sizes (60-150 mesh), PDMS prepolymer liquid was printed onto PET release film substrates and cured at 80℃ for 40 min to obtain cured films of different thicknesses (2.79μm, 1.55μm, 0.42μm).

[0041] S3, Ethanol-assisted non-destructive film removal: Cut the cured film to a size that matches the stainless steel mesh cap. Spray ethanol (wetting liquid) at the opening to eliminate van der Waals forces between the film and the substrate. After waiting for 3-5 seconds, remove it completely to obtain the PDMS film.

[0042] S4. Component Assembly: The PDMS film is flatly covered on the stainless steel mesh cap, and the interface air is gently pressed out to make it fit tightly. Then the film-coated mesh cap is inserted into the stainless steel shell to obtain a moisture-resistant and poison-resistant sensor device.

[0043] In some specific implementations, a secondary film thickness control process is also included, specifically: applying a gas pressure of kilopascal level (400-700 Pa) to the PDMS film from the stainless steel mesh cap side, so that the film undergoes controllable stretching and thinning within the elastic range.

[0044] During the secondary film thickness control process, a gas sensor static tester is used to test the device's response value to the target ethanol gas, response recovery time, baseline stability, and anti-interference ability in real time. By adjusting the applied gas pressure and holding time, the optimal ethanol permeation flux and sensor comprehensive response characteristics are obtained, and finally the best film thickness control process parameters matching the actual detection requirements are determined.

[0045] This invention employs screen printing technology in the fabrication of sensor components, which has the following advantages compared to methods such as inkjet printing and electrospinning: Screen printing equipment is simple and easy to operate. The wet film thickness can be precisely adjusted by changing the mesh count of the screen and the number of coatings. The film thickness repeatability after curing is high. After the PDMS film produced by screen printing is cured on a flat substrate, the film layer is dense and free of pinholes, and the interfacial adhesion with the substrate is moderate. After being wetted with ethanol, it can be easily and completely peeled off, and the film transfer success rate is close to 100%, which solves the problem of non-destructive peeling of films produced by electro-spraying and electrospinning. Screen printing is easy to pattern, and can directly print films that match the shape of stainless steel mesh caps, reducing subsequent cutting processes.

[0046] In the ethanol (alcohol)-assisted film peeling process used in this invention, alcohol rapidly penetrates into the interface between the film and the substrate, eliminating van der Waals forces, achieving complete wetting, and ensuring the non-destructive separation of large-area micron-scale PDMS films.

[0047] The further optimized solution of this invention employs a secondary film thickness control process. By adjusting the applied gas pressure and the duration of action, the film thickness reduction can be precisely controlled at the micrometer level, shortening the transmembrane diffusion path of target gas molecules (such as ethanol) and selectively increasing the permeation flux of target gas molecules. This method replaces the lag and destructive nature of traditional offline SEM film thickness characterization, achieving online linkage optimization between film thickness control and device performance: through real-time data feedback from a static testing instrument, the balance point between the response sensitivity and selectivity of target gas molecules can be accurately located, avoiding the decline in moisture resistance / silicon poisoning resistance caused by excessive thinning, while significantly shortening the process parameter optimization cycle.

[0048] Figure 1 This is a schematic diagram of the manufacturing process of the sensor device of the present invention.

[0049] Example 1 Fabrication of 60-mesh PDMS film sensor: Preparation of S1 and PDMS prepolymer solution: Measure 10 mL of PDMS prepolymer and 1 mL of crosslinking agent, pour them into a beaker, stir for 5 min until they are mixed evenly, place the beaker in an ultrasonic cleaner and sonicate for 10 min to remove air bubbles from the mixture, remove it and let it stand for 30 min to obtain PDMS prepolymer solution.

[0050] S2, Screen Printing for Film Formation: A 60-mesh screen was used to pour the PDMS prepolymer onto the screen and then uniformly spread it onto the surface of the PET release film using a squeegee. The film was then placed in an 80°C oven for 40 minutes to cure, resulting in a cured film with a thickness of 2.79 μm.

[0051] S3, Ethanol-assisted non-destructive film removal: Cut the cured film into circular pieces that match the stainless steel mesh cap using a stainless steel knife. Gently peel off one corner of the film with pointed tweezers, spray a small amount of ethanol at the opening, wait 3-5 seconds, and then slowly peel the entire film off the release film along the opening to obtain the PDMS film.

[0052] S4. Component Assembly: The peeled PDMS film is flattened and covered onto a stainless steel mesh cap with a slightly smaller diameter. The air at the interface is gently pressed out to make it fit tightly. Finally, the film-coated mesh cap is inserted into the stainless steel housing to obtain a 60-mesh PDMS film sensor.

[0053] Example 2 Fabrication of 100-mesh PDMS film sensor: Preparation of S1 and PDMS prepolymer solution: Measure 10 mL of PDMS prepolymer and 1 mL of crosslinking agent, pour them into a beaker, stir for 5 min until they are mixed evenly, place the beaker in an ultrasonic cleaner and sonicate for 10 min to remove air bubbles from the mixture, remove it and let it stand for 30 min to obtain PDMS prepolymer solution.

[0054] S2, Screen Printing for Film Formation: A 100-mesh screen was selected, and the PDMS prepolymer solution was poured onto the screen. It was then uniformly coated onto the surface of the PET release film with a squeegee. The film was then placed in an 80℃ oven for 40 minutes to cure, resulting in a cured film with a thickness of 1.55μm.

[0055] S3, Ethanol-assisted non-destructive film removal: Cut the cured film into circular pieces that match the stainless steel mesh cap using a stainless steel knife. Gently peel off one corner of the film with pointed tweezers, spray a small amount of ethanol at the opening, wait 3-5 seconds, and then slowly peel the entire film off the release film along the opening to obtain the PDMS film.

[0056] S4. Component Assembly: The peeled PDMS film is flattened and covered onto a stainless steel mesh cap with a slightly smaller diameter. The air at the interface is gently pressed out to make it fit tightly. Finally, the film-coated mesh cap is inserted into the stainless steel housing to obtain a 100-mesh PDMS film sensor.

[0057] Example 3 Fabrication of 150-mesh PDMS film sensor: Preparation of S1 and PDMS prepolymer solution: Measure 10 mL of PDMS prepolymer and 1 mL of crosslinking agent, pour them into a beaker, stir for 5 min until they are mixed evenly, place the beaker in an ultrasonic cleaner and sonicate for 10 min to remove air bubbles from the mixture, remove it and let it stand for 30 min to obtain PDMS prepolymer solution.

[0058] S2, Screen Printing for Film Formation: A 150-mesh screen was used to pour the PDMS prepolymer onto the screen and then uniformly spread it onto the surface of the PET release film using a squeegee. The film was then placed in an 80°C oven for 40 minutes to cure, resulting in a cured film with a thickness of 0.42 μm.

[0059] S3, Ethanol-assisted non-destructive film removal: Cut the cured film into circular pieces that match the stainless steel mesh cap using a stainless steel knife. Gently peel off one corner of the film with pointed tweezers, spray a small amount of ethanol at the opening, wait 3-5 seconds, and then slowly peel the entire film off the release film along the opening to obtain the PDMS film.

[0060] S4. Component Assembly: The peeled PDMS film is flattened and covered onto a stainless steel mesh cap with a slightly smaller diameter. The air at the interface is gently pressed out to make it fit tightly. Finally, the film-coated mesh cap is inserted into the stainless steel housing to obtain a 150-mesh PDMS film sensor.

[0061] Example 4 Fabrication of PDMS membrane sensor devices: S1-S3, same as in Example 2.

[0062] S4. Flatten the peeled PDMS membrane onto a stainless steel mesh cap with a slightly smaller diameter, gently press to expel interfacial air, and ensure a tight fit. Then, insert the membrane-coated mesh cap into the stainless steel housing. Apply different kPa-level (4kPa, 5kPa, 6kPa, or 7kPa) gas pressures to the PDMS membrane from one side of the stainless steel mesh cap. Control the distance between the gas source outlet and the membrane surface so that the pressure on the membrane surface is approximately 400-700Pa, causing the membrane to undergo controllable stretching and thinning within its elastic range. Hold the pressure for 2 minutes and then release the pressure to obtain the PDMS membrane sensor.

[0063] Comparative Example 1 Measure 10 mL of Dow Corning DC184 main agent A and 4 mL of curing agent B, pour them into a beaker, stir for 5 min until homogeneous, place the beaker in an ultrasonic cleaner and sonicate for 10 min to remove air bubbles from the mixture, remove and let stand for 30 min to obtain PDMS polymer. Transfer 0.5 mL of the polymer into a 1 mL Ming'an Kang syringe, using a 2.0 nozzle, a propulsion speed of 118 μm / min, and adjust the voltage to 4 kV.

[0064] Comparative Example 2 Measure 10 mL of Dow Corning DC184 main agent A and 1 mL of curing agent B, pour them into a beaker, stir for 5 min until they are evenly mixed, place the beaker in an ultrasonic cleaner and sonicate for 10 min to remove air bubbles from the mixture, remove it and let it stand for 30 min to obtain PDMS polymer; weigh 1.5 g of PVP and mix it with 8 ml of ethanol and 2 ml of deionized water, stir at 60 °C for 4 h to obtain a transparent solution, mix PVP and PDMS at a mass ratio of 4:1 and stir for 2 h; take 3 ml of the mixed solution into a 10 ml Ming'an Kang syringe, adjust the voltage to 15 kV, keep the needle 15 cm away from the receiving plane, and let the solution fall naturally by gravity.

[0065] In Comparative Example 1 and Comparative Example 2, PDMS films were prepared by electro-inking and electrospinning, respectively.

[0066] Under electro-spray printing conditions, PDMS prepolymer is sprayed into filaments under a high-voltage electric field and deposited on the receiving substrate to form a thin film. However, the resulting film has poor thickness uniformity (thin at the edges and thick in the center), and the film adheres too strongly to the substrate. Even with ethanol wetting, it is difficult to peel off completely, and the torn film is mostly broken.

[0067] The PDMS fiber membrane prepared by electrospinning has a loose structure with a large number of micron-sized pores, and lacks selective permeability to ethanol and water vapor; the fiber membrane has low mechanical strength and tears when picked up with tweezers, making it impossible to reliably transfer to the mesh cap.

[0068] In contrast, the screen printing method used in this invention produces a dense, uniform film layer with a near 100% film removal success rate, and is simple to operate with low equipment costs.

[0069] Test case The cured films prepared in Examples 1-3 were immersed in liquid nitrogen and fractured. After gold sputtering treatment of the fracture surface, the cross-sectional morphology was observed and the film thickness was measured using a scanning electron microscope. Measurements were taken at five different locations on each film, and the average value was taken as the film thickness corresponding to that mesh size. The results are as follows: Figure 2 As shown.

[0070] Figure 2The figures show the thicknesses of the cured films prepared in Examples 1-3, where a represents Example 3, b represents Example 2, and c represents Example 1. As can be seen from the figures, the film thicknesses obtained using a 60-mesh screen are 2.79 ± 0.2 μm, 100-mesh is 1.55 ± 0.2 μm, and 150-mesh is 0.42 ± 0.01 μm. Subsequent COMSOL simulations and examples will use this thickness as a benchmark.

[0071] To systematically study the regulation of membrane thickness by gas pressure, this invention first conducted COMSOL Multiphysics simulation, temporarily using a membrane thickness of 500 μm. The pressure applied to the membrane surface was gradually increased from 0 to 700 Pa, and the changes in ethanol permeation under different pressures are shown in Table 1.

[0072] Figure 3 This is a COMSOL simulation model diagram of PDMS film thickness controlled by air pressure.

[0073]

[0074] As can be seen from the table, within the range of 0-300 Pa, the ethanol permeation flux only increases from 3.2682 × 10⁻⁶ Pa. -6 mol·m -2 ·s -1 A slight increase to 3.3363 × 10 -6 mol·m -2 ·s -1 The relative increase was less than 2%; when the gas pressure further increased to 400-700 Pa, the flux basically stabilized at about 3.34 × 10⁻⁶. -6 mol·m -2 ·s -1 There were no further significant changes. This indicates that under a micro-pressure of several hundred Pascals, the elastic deformation of the PDMS membrane was minimal, and the membrane thickness was hardly reduced effectively. Therefore, the diffusion path length of ethanol molecules remained essentially unchanged, and the permeation flux could not be substantially improved.

[0075] The simulation results theoretically reveal that to achieve a significant increase in ethanol permeation flux, a sufficiently high gas pressure must be applied to reduce the thickness of the PDMS membrane to the micrometer level.

[0076] In the secondary pressure control step of actual sensor fabrication, this invention increases the working pressure to the kilopascal level (4-7 kPa) to produce significant film thickness reduction and corresponding enhanced ethanol response. Experiments confirm that within this pressure range, the PDMS film thickness can be uniformly reduced to the target value, and the sensor's response to ethanol monotonically increases with increasing pressure, which is highly consistent with the trend predicted by simulation.

[0077] Figure 4The figure shows the simulated distribution of ethanol permeation concentration. A two-dimensional axisymmetric model was built using COMSOL Multiphysics software. The geometric model consists of a gas diffusion layer, a PDMS film layer, and a gas diffusion path from top to bottom, with an overall width of 3000 μm and a length of 6000 μm. The physics fields of the "Dilute Mass Transport," "Solid Mechanics," and "Deformed Geometry" modules were selected to solve the diffusion-convection equations of ethanol within the film. The film thickness parameters were set to 100 μm, 200 μm, 300 μm, 400 μm, and 500 μm.

[0078] The simulation results of the relationship between PDMS membrane thickness and permeation flux are shown in Table 2.

[0079]

[0080] As shown in Table 2, the steady-state concentration and flux of ethanol on the downstream side of the membrane significantly increased with decreasing membrane thickness. When the membrane thickness was gradually reduced from 500 μm to 100 μm, the ethanol permeation flux increased from 2.1755 × 10⁻⁶ to 2.1755 × 10⁻⁶. -6 mol·m -2 ·s -1 Monotonically increasing to 6.4475 × 10 -5 mol·m -2 ·s -1 The increase was approximately 29.6 times. In contrast, within the same membrane thickness variation range, the increase in water vapor permeation flux was extremely low, far less than the increase in ethanol flux. This stark contrast demonstrates that thinning the PDMS membrane can selectively and significantly enhance the transmembrane mass transfer of ethanol molecules, while having a very limited effect on enhancing the permeation of small molecule interfering substances such as water vapor. This result provides clear theoretical guidance for achieving highly selective ethanol permeation by controlling membrane thickness, confirming the scientific rigor and advancement of the ultrathin film layer and gas pressure secondary thinning process employed in this invention.

[0081] Humidity interference resistance test: Fabrication of bare mesh sensor: Cut stainless steel mesh of appropriate size and place it in a mold. Deform it by extrusion to obtain stainless steel mesh cap. Then insert the stainless steel mesh cap into the stainless steel shell to obtain bare mesh sensor.

[0082] The embodiment and the bare-mesh sensor were subjected to humidity interference resistance testing, and the steps are as follows: The effect of humidity on the sensor is indirectly reflected by testing the change in resistance (i.e., response value) of the sensor when a detection gas is introduced using a gas static tester. First, the sensor is inserted into the detection card of the gas static tester, a suitable load card (100K) is selected, the working voltage is 5.2V, and the measurement voltage is 5V. The test begins when the curve stabilizes. During the test, the cover of the tester is closed to keep it static. Then, the desired target gas is introduced, or the desired target gas in liquid form is heated on the heating platform to obtain the target gas. Second, the humidity of the test environment is adjusted to 20%, 40%, 60%, and 80% by evaporating an appropriate amount of water vapor on the heating platform. Then, 50ppm of ethanol gas is introduced. After reaching the peak and stabilizing, the cover is opened, and the response curve is waited for to return to stability. During this process, the change in response value is recorded to obtain the response curve.

[0083] Figure 5 The figure shows the response curves of the bare mesh sensor to 50 ppm ethanol under different humidity conditions. As can be seen from the figure, the response value of the bare mesh sensor continuously decreases with increasing ambient humidity, and its response curve exhibits significant fluctuations and spikes. According to Table 3, under high humidity conditions of 80% RH, the response value of the bare mesh sensor significantly decreased from 3.86 at 40% RH to 3.37, a decrease of 12.7%. This phenomenon indicates that high concentrations of water molecules strongly compete with ethanol for adsorption on the surface of the sensitive material. This not only occupies active sites, leading to a decrease in response value, but also causes instability in the electrical signal of the sensitive layer due to the continuous adsorption-desorption dynamic process of water molecules, making it impossible for the sensor to output a reliable and stable detection signal under humidity interference.

[0084]

[0085] Figure 6The figures show the response curves of the sensors in Examples 1-3 and the bare mesh sensor to ethanol gas under different humidity levels. In the figures, a represents 20% humidity, b represents 40% humidity, c represents 60% humidity, and d represents 80% humidity. The screen-printed 60-mesh sensor represents Example 1, the screen-printed 100-mesh sensor represents Example 2, the screen-printed 150-mesh sensor represents Example 3, and the sensor without the PDMS film represents the bare mesh sensor. In contrast, the PDMS film-loaded sensors (Examples 1-3) exhibit smooth and stable response curves under the same high humidity conditions, with almost no baseline drift. The response and recovery times are essentially consistent with those under low humidity conditions, and no obvious water molecule interference is observed. Example 2 (approximately 1.55 μm thick) shows the best performance: the response value remains stable between 3.60 and 3.84 within the 40%–80% RH range, with a maximum fluctuation of only about 6.4%. At 80% RH, the response value reaches as high as 3.83, showing almost no attenuation compared to 3.60 at 40% RH. Its response curves exhibit high signal-to-noise ratios, thorough recovery, and no tailing phenomenon across the entire humidity range. The response curve of Example 3 (0.42μm) is also stable, while the response of Example 1 (2.79μm) is lower at low humidity of 20%RH, but interference fluctuations are basically eliminated above 40%RH.

[0086] The above comparisons fully demonstrate that PDMS membranes, utilizing their inherent hydrophobic properties and dissolution-diffusion selective permeation mechanism, effectively block the penetration of the vast majority of water molecules into the sensitive layer, thus suppressing the interference of competitive adsorption and dynamic disturbances of water molecules on the sensor signal at the source. Among these, the 1.55μm thick PDMS membrane fabricated using 100-mesh screen printing achieves the optimal balance between ethanol permeation efficiency and water barrier capability, ensuring high response sensitivity while completely eliminating interference phenomena such as curve fluctuations, baseline drift, and recovery delay under high humidity environments. This demonstrates significant necessity and practical value for improving the signal quality, detection accuracy, and long-term reliability of semiconductor gas sensors in real-world high-humidity environments.

[0087] The silicon poisoning resistance test of the sensor device and bare grid sensor in Example 2 includes the following steps: To verify the protective effect of the PDMS membrane against silicon vapor poisoning, the bare mesh sensor and the sensor from Example 2 were placed in a test environment containing 20 ppm hexamethyldisiloxane (HMDSO) for 40 minutes to accelerate silicon poisoning treatment. The sensor's response to 50 ppm ethanol was measured before and after poisoning. Three parallel samples were set up for each group, and the attenuation ratio and average attenuation ratio were calculated. The results are as follows: Figure 7 As shown in Table 4.

[0088] Figure 7 The graphs show the response changes of the sensor device and the bare mesh sensor in Example 2 to 50 ppm ethanol before and after silicon vapor poisoning.

[0089]

[0090] Figure 7 In Table 4, membrane-free groups 1-3 are bare mesh sensors, and PDMS membrane 1-PDMS membrane 3 are from Example 2.

[0091] Depend on Figure 7 As can be seen from Table 4: After silicon poisoning treatment, the response attenuation ratios of the three parallel samples of the membrane-free sensor were 27.1%, 20.25%, and 21.75%, respectively, with an average attenuation ratio as high as 23.03%, indicating a significant and irreversible decrease in response value. This suggests that without effective protection, silicon vapor molecules directly contacted and poisoned the surface of the sensitive material, forming a dense SiO2 coating that occupied and destroyed a large number of ethanol adsorption active sites, leading to a significant degradation in sensor sensitivity.

[0092] In contrast, after the same silicon poisoning treatment, the attenuation ratios of the three parallel samples with PDMS membranes were 20.34%, -1.77% (i.e., the response value remained basically unchanged, within the normal test fluctuation range), and 16.57%, respectively, with an average attenuation ratio of only 11.71%, less than half that of the unmembrane group. Among them, the response values ​​of PDMS membrane group 2 before and after poisoning were 3.96 and 4.03, respectively, with almost no attenuation, strongly demonstrating that PDMS membranes have excellent barrier protection capabilities against silicon vapor.

[0093] The anti-silicon poisoning mechanism of PDMS membrane lies in its dense polymer cross-linking network and dissolution-diffusion mass transfer mechanism, which has a significant sieving and dissolution barrier effect on silicon vapor molecules such as HMDSO with large molecular dynamic diameter and low polarity. This greatly reduces the concentration of silicon molecules that penetrate to the surface of the sensitive layer, inhibits the occurrence and spread of silicon poisoning reaction from the source, and effectively protects the active sites of the sensitive material.

[0094] Based on the above data and mechanism analysis, loading a PDMS film on the outside of the sensor is of significant necessity and irreplaceable practical value in resisting silicon vapor poisoning and maintaining the long-term detection sensitivity and working stability of the sensor.

[0095] Gas selectivity test: First, set up the sensor with the PDMS film load and the bare mesh sensor on the GTR-2 gas static analyzer, adjust the operating voltage to 5.2V, the test voltage to 5.0V, and select a load card of 1×10. 5 Ω, ethanol, formaldehyde and acetone 50ppm were introduced respectively, and the response values ​​and response curves after introduction were recorded.

[0096]

[0097] Based on the absolute values ​​of the responses in Table 5, the 100-mesh membrane (Example 2) showed the highest response to ethanol (4.17), the 60-mesh membrane (Example 1) was comparable (4.16), and the 150-mesh membrane (Example 3) showed the lowest (2.80). In terms of selectivity, the 60-mesh membrane exhibited the best performance with an ethanol / formaldehyde selectivity of approximately 2.43 and an ethanol / acetone selectivity of approximately 2.39; the corresponding ratios for the 100-mesh membrane were 1.74 and 1.56, respectively; and the 150-mesh membrane was the worst.

[0098] Figure 8 The graphs show the response curves for different gases. In the graphs, the screen-printed -60 mesh sensor represents Example 1, the screen-printed -100 mesh sensor represents Example 2, the screen-printed -150 mesh sensor represents Example 3, and the sensor without the PDMS film represents a bare mesh sensor. All sensors with PDMS film (Examples 1-3) exhibit varying degrees of "sloping S-shaped" distortion in their acetone response curves: a step-like rise in the response, continuous signal fluctuation during the steady state, and a significant tailing during the recovery phase. This phenomenon indicates a complex interaction between acetone and the PDMS film, and that the 100-mesh film achieves the optimal balance between suppressing acetone curve distortion and maintaining a high ethanol response.

[0099] Based on the combined performance test and simulation results, the 1.55μm thick PDMS film sensor device fabricated by 100-mesh screen printing exhibits the best performance in core indicators such as ethanol response sensitivity, humidity interference resistance stability, silicon poisoning resistance, and gas selectivity.

[0100] To verify the effect of the secondary film thickness control process on the sensor's ethanol response performance, the sensor's ethanol response performance before and after the treatment (Examples 2 and 4) was compared: Using Example 2 as the control group (without the secondary film thickness control process) and Example 4 as the experimental group, the effect of the secondary film thickness control process on the response value of ethanol was studied. Figure 9 As shown in Table 6, the method is as follows: The sensor with an unpressurized PDMS membrane housing was placed on the GTR-2 gas sensor static tester. During the experiment, the PDMS membrane housing was replaced with one that had been regulated under different pressures. The sensor's operating voltage was 5.2V, the test voltage was 5V, and the load card was selected as 1x10. 5 Ω, 50 ppm of ethanol was introduced and its response value and response curve were recorded.

[0101] Figure 9 The response curves of Example 2 and Example 4 are compared.

[0102]

[0103] In the table, the output distance between the gas source and the sensor is 16 cm. When the output pressure of the gas source is 4 kPa, the gas pressure acting on the PDMS membrane surface is approximately 400 Pa; when the output pressure of the gas source is 5 kPa, the gas pressure acting on the PDMS membrane surface is approximately 500 Pa; when the output pressure of the gas source is 6 kPa, the gas pressure acting on the PDMS membrane surface is approximately 600 Pa; and when the output pressure of the gas source is 7 kPa, the gas pressure acting on the PDMS membrane surface is approximately 700 Pa.

[0104] From Table 6 and Figure 9 Data analysis shows that: The secondary membrane thickness adjustment process significantly enhances the response. Without pressure (Example 2), the average response value of the sensor was only 1.537. After treatment with pressures of 400 Pa, 500 Pa, 600 Pa, and 700 Pa, the average response values ​​increased to 1.805, 1.825, 1.875, and 2.037, respectively, representing increases of 17.4%, 18.7%, 22.0%, and 32.5%. The response value increases monotonically with increasing membrane pressure, indicating that pressure-induced membrane thinning effectively shortens the transmembrane diffusion path of target gas molecules (such as ethanol), increasing the permeate flux and thus significantly enhancing the sensor response.

[0105] The relative standard deviation of the three parallel data sets (1.920, 1.884, and 1.821) in the 600 Pa treatment group was only 2.7%, indicating the best process repeatability. Secondary pressure regulation, under appropriate pressure, not only improved the response value but also significantly enhanced response consistency and process repeatability.

[0106] The COMSOL Multiphysics simulations above show that the ethanol permeation flux of the screen-printed uniform membrane remains almost unchanged within the low pressure range of 0–300 Pa. In Example 4, a pressure range of 400–700 Pa was used, and a response improvement of 17.4%–32.5% was observed within this range.

[0107] Considering both the magnitude of the response enhancement and the repeatability of the process, 600 Pa is the optimal pressure parameter. Under this condition, the sensor response value is 22.0% higher than that of the unpressurized group, and the RSD of the three parallel tests is only 2.7%, which meets the requirements for performance consistency in mass production.

[0108] In summary, the secondary membrane thickness control process requires only a few hundred Pascals of membrane surface pressure to significantly improve the sensor's response performance to target gas molecules through multiple mechanisms, including eliminating interfacial mass transfer resistance, homogenizing membrane thickness distribution, and elastic thinning. 600 Pa is the optimal parameter balancing high response and excellent repeatability. This test and simulation study corroborate each other, forming a complete evidence chain of pressure-controlled membrane thickness and enhanced target gas molecule permeation, fully verifying the scientific validity and practicality of the secondary membrane thickness control process of this invention.

[0109] Through four systematic tests—anti-humidity interference, anti-silicon poisoning, gas selectivity, and secondary pressure regulation effect—combined with COMSOL multiphysics simulation results, the metal mesh shell-loaded PDMS film sensor device prepared in this invention comprehensively solves the environmental interference problem of semiconductor gas sensors. Ethanol was used as the target gas molecule in the experiment. Anti-humidity interference performance: The bare mesh sensor showed a 12.7% response decay to 50ppm ethanol in a high humidity environment of 80%RH, and the signal fluctuation was obvious; the sensor loaded with a 100-mesh PDMS membrane (1.55μm) (Example 2) showed a response fluctuation of only 6.4% in the range of 40%~80%RH, with a smooth curve and no drift, achieving the optimal balance between ethanol permeation efficiency and moisture barrier capability.

[0110] Gas selectivity: The 60-mesh PDMS membrane (Example 1) showed the best ethanol selectivity (ethanol / formaldehyde = 2.43, ethanol / acetone = 2.39); the 100-mesh PDMS membrane (Example 2) had the highest ethanol response value (4.17) and could effectively suppress the "slanted S-shaped" distortion of the acetone response curve, thus exhibiting the best overall performance.

[0111] Effect of secondary pressure regulation: In Example 4, the sensor obtained by applying a membrane pressure of 400~700Pa showed a response value improvement of 17.4%~32.5% compared with the unpressurized group (Example 2); 600Pa (air source output 6kPa, distance 16cm) was the optimal parameter, with a response improvement of 22.0% and the best process repeatability (RSD=2.7%). This regulation improves performance through multiple mechanisms such as eliminating interfacial gaps, homogenizing membrane thickness, and elastic thinning, which complements and verifies the simulation results.

[0112] Overall, the basic scheme for preparing a 1.55μm thick PDMS film by 100-mesh screen printing (Example 2), combined with secondary adjustment of the 600Pa film surface pressure, can achieve the best balance between ethanol response sensitivity, anti-interference stability and process repeatability.

[0113] Antistatic performance test: Resistivity formula: ; In the formula, ρ is resistivity, R is resistance, L is the length of the sample through which the current flows, and S is the cross-sectional area (S=W×d, W is the sample width, and d is the sample thickness).

[0114] Material antistatic classification: a) Conductor: ρ<10 4 Ω·cm; b) Antistatic (dissipative material): ρ∈10 4 ~10 11 Ω·cm; The sample was a sheet of stainless steel mesh with a length of L=3cm, a width of W=2.5cm, and a thickness of d=0.008cm; the PDMS membrane used had a length of L=3cm, a width of W=2.5cm, and a thickness of d=0.001cm for easy measurement (to prevent the test clamp from breaking the membrane).

[0115] First, measure the resistance of the stainless steel mesh. The positive and negative electrodes are clamped at both ends of L=3cm. Start measuring and record the resistance value. Then, attach the PDMS film to the stainless steel mesh to obtain the stainless steel mesh / PDMS film. The positive and negative electrodes are the same as above. Start measuring and recording the resistance value of the stainless steel mesh / PDMS film.

[0116] The test instrument used was a UT8805N benchtop digital multimeter for measurement, and the results were... Figure 10 As shown.

[0117] Figure 10 The figures show the resistances of the stainless steel mesh and the stainless steel mesh / PDMS film, where a represents the stainless steel mesh and b represents the stainless steel mesh / PDMS film. As can be seen from the figure, the resistance of the stainless steel mesh is R1 = 0.184 Ω, and the resistance of the stainless steel mesh / PDMS film is R2 = 905960 Ω.

[0118] Using the resistivity formula above, we can calculate that the stainless steel mesh has a resistivity of ρ1 = 1.22 × 10⁻⁶. -3 Ω·cm, stainless steel mesh / PDMS film ρ2=6.795×10 3 Ω·cm; According to resistivity tests, the resistivity of the stainless steel mesh after being loaded with a PDMS film increases from ρ1 = 1.22 × 10⁻⁶ Ω·cm. -3 The Ω·cm increases to ρ² = 6.795 × 10⁻⁶. 3 Although the capacitance is still within the range of conductive materials, it is quite close to the lower limit of electrostatic dissipative materials. This device can conduct static charge and suppress the accumulation of large amounts of charge, thus possessing electrostatic control capabilities.

[0119] The various embodiments in this specification are described in a progressive manner, with each embodiment focusing on the differences from other embodiments. The same or similar parts between the various embodiments can be referred to each other.

[0120] The above description of the disclosed embodiments enables those skilled in the art to make or use the invention. Various modifications to these embodiments will be readily apparent to those skilled in the art, and the general principles defined herein may be implemented in other embodiments without departing from the spirit or scope of the invention. Therefore, the invention is not to be limited to the embodiments shown herein, but is to be accorded the widest scope consistent with the principles and novel features disclosed herein.

Claims

1. A method for fabricating a sensor device with a metal mesh shell loaded with a PDMS film, characterized in that the steps include... include: The PDMS prepolymer and crosslinking agent are mixed evenly to obtain the PDMS prepolymer solution; The PDMS prepolymer solution was printed onto a PET release film substrate using screen printing, cured, and then peeled off non-destructively with ethanol to obtain a PDMS film. The PDMS film is covered on a stainless steel mesh cap, and after venting and bonding, it is inserted into a stainless steel shell to obtain the sensor device.

2. The preparation method according to claim 1, characterized in that, The volume ratio of the PDMS prepolymer to the crosslinking agent is 10:1; The PDMS prepolymer and crosslinking agent are Dow Corning DC184, wherein the PDMS prepolymer is the main agent A in Dow Corning DC184, and the crosslinking agent is the curing agent B in Dow Corning DC184.

3. The preparation method according to claim 1, characterized in that, The screen printing stencil used for the screen printing film formation has a mesh count of 60-150.

4. The preparation method according to claim 1, characterized in that, The curing temperature is 75-85℃ and the time is 30-50 minutes.

5. The preparation method according to claim 1, characterized in that, The steps for ethanol-assisted non-destructive film removal include: spraying ethanol at the opening, waiting 3-5 seconds, and then completely removing the PDMS film.

6. The preparation method according to claim 1, characterized in that, The thickness of the PDMS film is 0.4-2.8 μm.

7. The preparation method according to claim 1, characterized in that, After the stainless steel shell is inserted, a secondary film thickness adjustment process is also included.

8. The preparation method according to claim 7, characterized in that, The secondary thickness control process includes: applying a gas pressure of 400-700 Pa to the PDMS film from the stainless steel mesh cap side, causing the film to undergo controllable stretching and thinning within the elastic range, and testing the treated PDMS film to explore the effect of the elastic deformation of the PDMS film on the permeation of the target gas.

9. A sensor device with a metal mesh shell supporting a PDMS film, characterized in that, The sensor with the PDMS film loaded on the metal mesh shell is prepared by the preparation method according to any one of claims 1-8.

10. The application of a sensor device with a metal mesh shell loaded with a PDMS film as described in claim 9 in gas detection.